PENGEMBANGAN BUDIDAYA IKAN HIAS DI DESA TONJONG KABUPATEN BOGOR - Panggabean, Donwill; Sapuriningsih, Chikita Lestari; Hotman, Jan; Saleha, Eha (Jurnal Abdi Insani, 2024)
The economy of local communities can be improved through the involvement of the community itself. Micro, small and medium enterprises (MSME) are one example. MSME are social institutions that function as a forum and means of development of every member of society, growing according to a sense of social responsibility from, for, and by the community. Community groups that are members of the "Agro Garuda Sakti Jaya" are located in Tonjong Village, Tajur Halang District, Bogor Regency, the economic business activities carried out are the cultivation of freshwater ornamental fish Neon Tetra, Rasbora Harlequin, and Rainbow Fish. The purpose of this community empowerment activity is to improve the skills of the Agro Garuda Sakti Jaya through ornamental fish farming training, natural feed culture training, and water quality measurement training. Participatory Action Research (PAR) is the method used in this community empowerment activity. The results of the activity showed: 1) increased knowledge of partners about biofloc technology and skills in making biofloc ponds; 2) increased knowledge and skills of partners in doing good ornamental fish farming; 3) increased knowledge and skills of partners in conducting good natural feed culture; and 4) increase ornamental fish production by 40% from before the implementation of activities. This community empowerment activity has a positional impact, because partners are able to adopt biofloc technology, and are able to carry out ornamental fish farming and natural feed culture well.